Monitoring of Helicobacter pylori in chicken products - Abd Elhameed, Ghada A.; Ahmed, Asmaa R.; Gomaa, Walaa M. (Journal of Advanced Veterinary Research, 2024)
A total of 200 samples of chicken products collected randomly from Quesna and El-Bagour in Menoufia governorate. The collected samples were represented by chicken breast, thigh, gizzard and liver (50 of each) and subjected to bacteriological examination for detection of Helicobacter species particularly, Helicobacter pylori. Further, the effect of L. rhamnosus culture to control such serious pathogen contaminating chicken products was studied. Helicobacter spp detected in 4%, 6%, 12% and 20% of breast, thigh, gizzard and liver, respectively and H. pylori represent 4%, 4% 6% and 10% from this examined samples, respectively. H. pylori inoculated chicken fillet (1×106 /g) which are not treated with Lactobacillus rhamnosus (control +ve) showed increase in prevalence of H. pylori 1.0×106, 1.3×106, 1.9×106 and 2.4×106 at zero time, 1st day, 2nd day and 3rd day, respectively. While chicken fillets treated with L. rhamnosus (1x106 /g) Effect on prevalence of H. pylori inoculated into chicken fillets with a reduction percent of 35%, 52% and 69% but L. rhamnosus (1x107 /g) showed remarkable reduction of H. pylori prevalence with a reduction percent of 54%, 67% and 81% at 1st day, 2nd day and 3rd day, respectively. L. rhamnosus effected on virulence genes of H. pylori isolated from treated chicken fillet as L. rhamnosus (1x106/g) destructed cagA gene and L. rhamnosus (1x107/g) destructed cagA and vacA genes so using of Lactobacillus rhamnosus culture as a method of control has a good effect on prevalence of H. pylori and its virulence genes in chicken fillets and L. rhamnosus (1x107 /g) more effective than L. rhamnosus (1x106 /g).